1984
DOI: 10.1161/01.atv.4.5.489
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to free fatty acid increases the transfer of albumin across cultured endothelial monolayers.

Abstract: An initial exposure to high concentrations of free fatty acid increased the transfer of albumin across cultured endothelial monolayers. The rate and amount of albumin transfer was dependent on the oleic acid concentration to which the cultures were initially exposed, with 300 p.M producing the maximum transfer. The albumin transfer also increased with the increasing time of exposure to oleic acid, the maximum effect occurring during the first 24 hours. An exposure to 300 juM linoleic acid produced an even grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(74 citation statements)
references
References 29 publications
3
70
0
1
Order By: Relevance
“…However, Hennig and colleagues (10,(22)(23)(24)(25) found that linolenic acid and saturated fatty acids were less potent modulators than linoleic acid on endothelial barrier function and PG synthesis. Although the effects on smooth muscle and endothelial cells are not necessarily transferable to hepatic cells, the above considerations led us to choose linoleic acid as a first model to study NEFAs' effects on hepatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, Hennig and colleagues (10,(22)(23)(24)(25) found that linolenic acid and saturated fatty acids were less potent modulators than linoleic acid on endothelial barrier function and PG synthesis. Although the effects on smooth muscle and endothelial cells are not necessarily transferable to hepatic cells, the above considerations led us to choose linoleic acid as a first model to study NEFAs' effects on hepatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lens cells actively transport albumin from the apical to the basolateral compartment in a process that involves caveolae and clathrin-coated vesicles (167)(168)(169). Micromolar concentrations of unsaturated fatty acids are cytotoxic to cultured bovine and human lens cells (170)(171)(172)(173)(174)(175). The aqueous humor of elderly patients who had cataracts contained micromolar levels of fatty acids and raises the possible involvement of these fatty acids in cataract formation.…”
Section: Systemic Fatty Acids and Cataractmentioning
confidence: 99%
“…The aqueous humor of elderly patients who had cataracts contained micromolar levels of fatty acids and raises the possible involvement of these fatty acids in cataract formation. In a number of pathophysiologic states related to cataract formation, fatty acid is elevated in blood [see references in ( 175,176 )]. Fatty acid exposure results in bleb formation where fatty acid molecules accumulate in the cells ( 174 ).…”
Section: Systemic Fatty Acids and Cataractmentioning
confidence: 99%
“…10 An oversupply of FFAs causes these cellular organelles to overproduce reactive oxygen species that can potentially contribute to the formation of lipid peroxidation products. 45,46 Lipolytic products have also been shown to enhance endothelial permeability, 47,48 whereas enhanced FFA metabolism in the heart can inhibit glucose oxidation. 49 The regulatory mechanisms governing changes in cardiac capillary-bound LPL in response to acute hypoinsulinemia are currently being investigated.…”
Section: Figurementioning
confidence: 99%